Basin development and provenance of the Lower to Middle Jurassic Ban Don Group in Indochina: Implications for the Jurassic Palaeo-Pacific subduction and drainage patterns - James W. Handschy; H. Tim Breitfeld; Bui Huy Hoang; Sarah W.M. George; William J. Schmidt; Juliane Hennig-Breitfeld; Michael B.W. Fyhn; Mette Olivarius; Nguyen Quang Tuan; Nguyen Thanh Tung; Do Van Linh; Dinh Quang Sang (Tectonophysics, 2026)

Geographic Variation in the Diet of Red Knot ( Calidris canutus ) Chicks Reflects Local Prey Communities - Reinier Blok; Mikhail K. Zhemchuzhnikov; Tim Oortwijn; Jannik Hansen; James A. Johnson; Niels Martin Schmidt; Judith D. L. van Bleijswijk; Elena Zhemchuzhnikova; Thomas K. Lameris; Jeroen Reneerkens; Tom Versluijs; Zachary M. Pohlen; et al. (Journal of Biogeography, 2026)
Aim To describe and compare the diets of an Arctic‐breeding shorebird, the Red Knot ( Calidris canutus ), across three geographically distinct breeding sites. We aimed to document the dietary patterns and identify key prey groups that characterise each population's foraging ecology. Location Northwest Alaska (Nome), Northeast Greenland (Zackenberg) and North‐Central Russia (Taimyr Peninsula). Taxon Red Knot (Aves: Calidris canutus ). Methods We characterised chick diet by applying COI DNA metabarcoding to faecal samples and quantified local prey availability using standardised arthropod pitfall trap sampling at the three Arctic breeding sites. We described and compared the dietary composition, diversity, and relative abundance of major prey taxa among locations. Results We found substantial geographical variation in the chick diet. Diptera was a major food source across all locations, but its constituent families and importance varied. In Taimyr, the diet was dominated by Tipulidae (crane flies), comprising nearly 50% of the relative read abundance (RRA). In contrast, chicks in Greenland consumed a diet dominated by Diptera (87.8%) that almost entirely lacked Tipulidae. The diet in Alaska was the most diverse, with balanced contributions from Diptera (28.5%), Coleoptera (22.3%), and Lepidoptera (23.2%), along with other invertebrate groups, including Agriolimacidae. Main Conclusions The diet of Red Knot chicks differed among the study sites and appeared to be shaped primarily by the local availability of arthropod prey. This foraging plasticity allows the species to breed successfully across a wide circumpolar range with a heterogeneous prey landscape. However, this distinct specialisation on local prey, particularly Tipulidae in Taimyr, may create a critical phenological vulnerability.

Enabling the circular nitrogen economy with organic and organo-mineral fertilisers - Susanne Schmidt; Vithya Krishnan; Harshi Gamage; Michael Walsh; Tim Huelsen; Juliane Wolf; Peter Wadewitz; Paul Jensen; Bianca Das; Nicole Robinson (Nutrient Cycling in Agroecosystems, 2025)
The circular nutrient economy repurposes organic (formerly alive, containing organic carbon) and inorganic (mineral) recycled materials as fertilisers and soil ameliorants, and halving nitrogen (N) waste is a global goal. Our focus was unavoidable food waste and garden waste (FOGO food organics garden organics) as suitable feedstock for compost and use for cropping. We hypothesised that to realise benefits of compost, organic and organo-mineral fertilisers (OF/OMF) must be optimised for target crops and biophysical environments. We explored compost and organic recyclates (dried bacterial biomass PPB, chicken litter manure) as N sources for vegetable, fruit and grain crops in controlled experiments with single or combinations of contrasting N release and carbon-to-N ratios of 20, 13.5 (compost), 13.5 (poultry manure), 6.1 (PPB) and 0.5 (mineral N). With standardised N input (0.5–1 g N/pot and plant), compost as the sole N source resulted in less yield than all other N sources, while suitable mixtures of organic recyclates with/without added mineral N matched the yield of crops grown with mineral N. Adding 5% compost to sand growth substrate modulated crop growth and phenology, increased tillering and panicle production, or accelerated fruit ripening. This confirmed effects beyond nutrient supply, likely crop-growth modulating substances are present. Exploring effects of crop species, N source and water supply confirmed statistically significant interactions on yield, biomass and N use efficiency (NUE). This means a robust strategy for optimising OF/OMF is testing target crops with compost and recyclates to identify crop-specific responses. We recommend that applying such strategy allows manufacturers targeting N-efficient OF/OMF to service the expanding market for recyclate-based organo-mineral fertilisers and soil ameliorants for the circular N economy.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Influence of 8-weeks of supervised static stretching or resistance training of pectoral major muscles on maximal strength, muscle thickness and range of motion - Tim Wohlann; Konstantin Warneke; Vincent Kalder; David G. Behm; Tobias Schmidt; Stephan Schiemann (European Journal of Applied Physiology, 2024)
Objectives Current research suggests static stretch-induced maximal strength increases and muscle hypertrophy with potential to substitute resistance-training routines. However, most studies investigated the plantar flexors. This study explored the effects of a static stretching program on maximal strength, hypertrophy and flexibility of the pectoralis major and compared the effects with those of traditional resistance training. Methods Eighty-one (81) active participants were allocated to either a static stretching, strength-training or control group. Pectoralis stretching was applied 15 min/day, 4 days per week for 8 weeks, while resistance training trained 3 days per week, 5 × 12 repetitions. Results There was an increase in all parameters (strength: p < 0.001, ƞ 2 = 0.313, muscle thickness: p < 0.001, ƞ 2 = 0.157–0.264, flexibility: p < 0.001, ƞ 2 = 0.316) and a time*group interaction (strength: p = 0.001, ƞ 2 = 0.154, muscle thickness: p = 0.008–0.001, ƞ 2 = 0.117–0.173, flexibility: p < 0.001, ƞ 2 = 0.267). Post-hoc testing showed no difference between both intervention groups regarding maximal strength and muscle thickness ( p = 0.905–0.983, d = 0.036–0.087), while flexibility increased in the stretching group ( p = 0.001, d = 0.789). Conclusion Stretching showed increases in maximal strength and hypertrophy, which were comparable with commonly used resistance training. Based on current literature, the influence of mechanical tension as the underlying mechanism is discussed. Furthermore, as equipment and comparatively long stretching durations are requested to induce meaningful strength increases in recreationally active participants, practical application seems limited to special circumstances.

Atmospheric CO2 emissions and ocean acidification from bottom-trawling - Trisha B. Atwood; Anastasia Romanou; Tim DeVries; Paul E. Lerner; Juan S. Mayorga; Darcy Bradley; Reniel B. Cabral; Gavin A. Schmidt; Enric Sala (Frontiers in Marine Science, 2024)
Trawling the seafloor can disturb carbon that took millennia to accumulate, but the fate of that carbon and its impact on climate and ecosystems remains unknown. Using satellite-inferred fishing events and carbon cycle models, we find that 55-60% of trawling-induced aqueous CO 2 is released to the atmosphere over 7-9 years. Using recent estimates of bottom trawling’s impact on sedimentary carbon, we found that between 1996-2020 trawling could have released, at the global scale, up to 0.34-0.37 Pg CO 2 yr -1 to the atmosphere, and locally altered water pH in some semi-enclosed and heavy trawled seas. Our results suggest that the management of bottom-trawling efforts could be an important climate solution.

Estimating plastic pollution in rivers through harmonized monitoring strategies - Tim H.M. van Emmerik; Sabrina Kirschke; Louise J. Schreyers; Shuvojit Nath; Christian Schmidt; Katrin Wendt-Potthoff (Marine Pollution Bulletin, 2023)

Barriers to plastic monitoring in freshwaters in the Global South - Sabrina Kirschke; Tim H.M. van Emmerik; Shuvojit Nath; Christian Schmidt; Katrin Wendt-Potthoff (Environmental Science & Policy, 2023)

Provenance of Oligocene–Miocene sedimentary rocks in the Cuu Long and Nam Con Son basins, Vietnam and early history of the Mekong River - H. Tim Breitfeld; Juliane Hennig-Breitfeld; Marcelle BouDagher-Fadel; William J. Schmidt; Kevin Meyer; Jeff Reinprecht; Terrence Lukie; Trinh Xuan Cuong; Robert Hall; Nils Kollert; Amy Gough; Rafika Ismail (International Journal of Earth Sciences, 2022)
The offshore Cuu Long (CLB) and Nam Con Son (NCSB) basins of SE Vietnam are two important Cenozoic hydrocarbon-bearing basins in the southern South China Sea (SCS), which can contribute to understanding the evolution of major SE Asian river systems, in particular the Mekong River. The Oligocene to Early Miocene basin fill of the Cuu Long Basin is dominated by sediment sourced locally from the Da Lat Zone basement on land. Sandstones have abundant Cretaceous detrital zircons and heavy mineral assemblages dominated by apatite and epidote. The Bach Ho Unconformity at c. 16 to 20.5 Ma marks a major provenance change and the overlying Middle to Late Miocene Con Son and Dong Nai formations were sourced by a large river system, which drained Indochina or even the Himalaya, resembling the present-day Mekong River. These formations have heterogeneous detrital zircon populations dominated by Triassic ages and zircon–rutile–tourmaline-dominated heavy mineral assemblages. The Oligocene Cau and Early Miocene Dua formations of the Nam Con Son Basin have a similar provenance to the CLB Con Son and Dong Nai formations, indicating a comparable drainage history of a large proto-Chao Phraya. At the Dua Unconformity at c. 15.4 to 17 Ma the Indochina provenance signature changes to a predominant Sibumasu signature. The early Mekong River evolution is suggested to have involved two river systems. A proto-Mekong 1 initially filled the CLB, while at the same time a proto-Chao Phraya River with a capture area into the Himalaya filled the Malay Basin and/or the NCSB. At the end of the Early Miocene drainage was completely reorganised, and the proto-Mekong 1 captured the headwaters of the proto-Chao Phraya and became the proto-Mekong 2, while the NCSB was filled by sediment from the Malay–Thai Peninsula. This major change marks a very important drainage reorganisation in the southern SCS region.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Biallelic variants in YRDC cause a developmental disorder with progeroid features - Julia Schmidt; Jonas Goergens; Tatiana Pochechueva; Annika Kotter; Niko Schwenzer; Maren Sitte; Gesa Werner; Janine Altmüller; Holger Thiele; Peter Nürnberg; Jörg Isensee; Yun Li; et al. (Human Genetics, 2021)
The highly conserved YrdC domain-containing protein (YRDC) interacts with the well-described KEOPS complex, regulating specific tRNA modifications to ensure accurate protein synthesis. Previous studies have linked the KEOPS complex to a role in promoting telomere maintenance and controlling genome integrity. Here, we report on a newborn with a severe neonatal progeroid phenotype including generalized loss of subcutaneous fat, microcephaly, growth retardation, wrinkled skin, renal failure, and premature death at the age of 12 days. By trio whole-exome sequencing, we identified a novel homozygous missense mutation, c.662T > C, in YRDC affecting an evolutionary highly conserved amino acid (p.Ile221Thr). Functional characterization of patient-derived dermal fibroblasts revealed that this mutation impairs YRDC function and consequently results in reduced t 6 A modifications of tRNAs. Furthermore, we established and performed a novel and highly sensitive 3-D Q-FISH analysis based on single-telomere detection to investigate the impact of YRDC on telomere maintenance. This analysis revealed significant telomere shortening in YRDC-mutant cells. Moreover, single-cell RNA sequencing analysis of YRDC-mutant fibroblasts revealed significant transcriptome-wide changes in gene expression, specifically enriched for genes associated with processes involved in DNA repair. We next examined the DNA damage response of patient’s dermal fibroblasts and detected an increased susceptibility to genotoxic agents and a global DNA double-strand break repair defect. Thus, our data suggest that YRDC may affect the maintenance of genomic stability. Together, our findings indicate that biallelic variants in YRDC result in a developmental disorder with progeroid features and might be linked to increased genomic instability and telomere shortening.

Seabird Migration Strategies: Flight Budgets, Diel Activity Patterns, and Lunar Influence - Anne-Sophie Bonnet-Lebrun; Maria P. Dias; Richard A. Phillips; José P. Granadeiro; M. de L. Brooke; Olivier Chastel; Thomas A. Clay; Annette L. Fayet; Olivier Gilg; Jacob González-Solís; Tim Guilford; Sveinn A. Hanssen; et al. (Frontiers in Marine Science, 2021)
Every year, billions of birds undertake extensive migrations between breeding and non-breeding areas, facing challenges that require behavioural adjustments, particularly to flight timing and duration. Such adjustments in daily activity patterns and the influence of extrinsic factors (e.g., environmental conditions, moonlight) have received much more research attention in terrestrial than marine migrants. Taking advantage of the widespread deployment in recent decades of combined light-level geolocator-immersion loggers, we investigated diel organisation and influence of the moon on flight activities during the non-breeding season of 21 migrant seabird species from a wide taxonomic range (6 families, 3 orders). Migrant seabirds regularly stopped (to either feed or rest) during migration, unlike some terrestrial and wetland birds which fly non-stop. We found an overall increase for most seabird species in time in flight and, for several species, also in flight bout duration, during migration compared to when resident at the non-breeding grounds. Additionally, several nocturnal species spent more of the day in flight during migration than at non-breeding areas, and vice versa for diurnal species. Nocturnal time in flight tended to increase during full moon, both during migration and at the non-breeding grounds, depending on species. Our study provides an extensive overview of activity patterns of migrant seabirds, paving the way for further research on the underlying mechanisms and drivers.

Increasing nutrient stress reduces the efficiency of energy transfer through planktonic size spectra - Angus Atkinson; Martin K.S. Lilley; Andrew G. Hirst; Andrea J. McEvoy; Glen A. Tarran; Claire Widdicombe; Elaine S. Fileman; E. Malcolm S. Woodward; Katrin Schmidt; Tim J. Smyth; Paul J. Somerfield (Limnology and Oceanography, 2021)
Size‐spectral approaches quantify the efficiency of energy transfer through food webs, but theory and field studies disagree over how changes in temperature, nutrients, and extreme weather impact on this efficiency. We address this at two scales: via 6 years of weekly sampling of the plankton size spectrum at the Plymouth L4 shelf sea site, and via a new, global‐scale, meta‐analysis of aquatic size spectra. The time series showed that with summertime nutrient starvation, the energy transfer efficiency from picoplankton to macroplankton decreased (i.e., steepening slopes of the size spectra). This reflected increasing dominance by small cells and their microbial consumers. The extreme storms in winter 2013/2014 caused high metazoan mortality, steep size‐spectral slopes, and reduced plankton biomass. However, recovery was within months, demonstrating an inbuilt resilience of the system. Both L4 and our meta‐analysis showed steep slopes of normalized size spectra (median −1.11). This reflects much lower values, either of trophic transfer efficiency (3.5%) or predator–prey mass ratio (569), compared to commonly quoted values. Results from the meta‐analysis further showed that to represent energy transfer faithfully, size spectra are best constructed in units of carbon mass and not biovolume, and span a mass range of > 10 7 . When this range is covered, both the meta‐analysis and time series show a dome‐shaped relationship between spectral slopes and plankton biomass, with steepening slopes under increasingly oligotrophic and eutrophic conditions. This suggests that ocean warming could decrease the efficiency of energy transfer through pelagic food webs via indirect effects of increasing stratification and nutrient starvation.

Increasing picocyanobacteria success in shelf waters contributes to long‐term food web degradation - Katrin Schmidt; Antony J. Birchill; Angus Atkinson; Robert J. W. Brewin; James R. Clark; Anna E. Hickman; David G. Johns; Maeve C. Lohan; Angela Milne; Silvia Pardo; Luca Polimene; Tim J. Smyth; et al. (Global Change Biology, 2020)
Continental margins are disproportionally important for global primary production, fisheries and CO 2 uptake. However, across the Northeast Atlantic shelves, there has been an ongoing summertime decline of key biota—large diatoms, dinoflagellates and copepods—that traditionally fuel higher tropic levels such as fish, sea birds and marine mammals. Here, we combine multiple time series with in situ process studies to link these declines to summer nutrient stress and increasing proportions of picophytoplankton that can comprise up to 90% of the combined pico‐ and nanophytoplankton biomass in coastal areas. Among the pico‐fraction, it is the cyanobacterium Synechococcus that flourishes when iron and nitrogen resupply to surface waters are diminished. Our field data show how traits beyond small size give Synechococcus a competitive edge over pico‐ and nanoeukaryotes. Key is their ability to grow at low irradiances near the nutricline, which is aided by their superior light‐harvesting system and high affinity to iron. However, minute size and lack of essential biomolecules (e.g. omega‐3 polyunsaturated fatty acids and sterols) render Synechococcus poor primary producers to sustain shelf sea food webs efficiently. The combination of earlier spring blooms and lower summer food quantity and quality creates an increasing period of suboptimal feeding conditions for zooplankton at a time of year when their metabolic demand is highest. We suggest that this nutrition‐related mismatch has contributed to the widespread, ~50% decline in summer copepod abundance we observe over the last 60 years. With Synechococcus clades being prominent from the tropics to the Arctic and their abundances increasing worldwide, our study informs projections of future food web dynamics in coastal and shelf areas where droughts and stratification lead to increasing nutrient starvation of surface waters.

The EU-ToxRisk method documentation, data processing and chemical testing pipeline for the regulatory use of new approach methods - Alice Krebs; Barbara M. A. van Vugt-Lussenburg; Tanja Waldmann; Wiebke Albrecht; Jan Boei; Bas ter Braak; Maja Brajnik; Thomas Braunbeck; Tim Brecklinghaus; Francois Busquet; Andras Dinnyes; Joh Dokler; et al. (Archives of Toxicology, 2020)
Hazard assessment, based on new approach methods (NAM), requires the use of batteries of assays, where individual tests may be contributed by different laboratories. A unified strategy for such collaborative testing is presented. It details all procedures required to allow test information to be usable for integrated hazard assessment, strategic project decisions and/or for regulatory purposes. The EU-ToxRisk project developed a strategy to provide regulatorily valid data, and exemplified this using a panel of > 20 assays (with > 50 individual endpoints), each exposed to 19 well-known test compounds (e.g. rotenone, colchicine, mercury, paracetamol, rifampicine, paraquat, taxol). Examples of strategy implementation are provided for all aspects required to ensure data validity: (i) documentation of test methods in a publicly accessible database; (ii) deposition of standard operating procedures (SOP) at the European Union DB-ALM repository; (iii) test readiness scoring accoding to defined criteria; (iv) disclosure of the pipeline for data processing; (v) link of uncertainty measures and metadata to the data; (vi) definition of test chemicals, their handling and their behavior in test media; (vii) specification of the test purpose and overall evaluation plans. Moreover, data generation was exemplified by providing results from 25 reporter assays. A complete evaluation of the entire test battery will be described elsewhere. A major learning from the retrospective analysis of this large testing project was the need for thorough definitions of the above strategy aspects, ideally in form of a study pre-registration, to allow adequate interpretation of the data and to ensure overall scientific/toxicological validity.

Future Ocean Observations to Connect Climate, Fisheries and Marine Ecosystems - Jörn O. Schmidt; Steven J. Bograd; Haritz Arrizabalaga; José L. Azevedo; Steven J. Barbeaux; John A. Barth; Tim Boyer; Stephanie Brodie; Juan José Cárdenas; Scott Cross; Jean-Noël Druon; Agneta Fransson; et al. (Frontiers in Marine Science, 2019)

Efficacy of novel selective NLRP3 inhibitors in human and murine retinal pigment epithelial cells - Luping Wang; Sarah Schmidt; Petra P. Larsen; Johanna H. Meyer; William R. Roush; Eicke Latz; Frank G. Holz; Tim U. Krohne (Journal of Molecular Medicine, 2019)

The diversity of population responses to environmental change - Fernando Colchero; Owen R. Jones; Dalia A. Conde; David Hodgson; Felix Zajitschek; Benedikt R. Schmidt; Aurelio F. Malo; Susan C. Alberts; Peter H. Becker; Sandra Bouwhuis; Anne M. Bronikowski; Kristel M. De Vleeschouwer; et al. (Ecology Letters, 2019)
The current extinction and climate change crises pressure us to predict population dynamics with ever‐greater accuracy. Although predictions rest on the well‐advanced theory of age‐structured populations, two key issues remain poorly explored. Specifically, how the age‐dependency in demographic rates and the year‐to‐year interactions between survival and fecundity affect stochastic population growth rates. We use inference, simulations and mathematical derivations to explore how environmental perturbations determine population growth rates for populations with different age‐specific demographic rates and when ages are reduced to stages. We find that stage‐ vs. age‐based models can produce markedly divergent stochastic population growth rates. The differences are most pronounced when there are survival‐fecundity‐trade‐offs, which reduce the variance in the population growth rate. Finally, the expected value and variance of the stochastic growth rates of populations with different age‐specific demographic rates can diverge to the extent that, while some populations may thrive, others will inevitably go extinct.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Multibeam sonar backscatter data processing - Alexandre C. G. Schimel; Jonathan Beaudoin; Iain M. Parnum; Tim Le Bas; Val Schmidt; Gordon Keith; Daniel Ierodiaconou (Marine Geophysical Research, 2018)

De novo FBXO11 mutations are associated with intellectual disability and behavioural anomalies - Daniel Fritzen; Alma Kuechler; Mona Grimmel; Jessica Becker; Sophia Peters; Marc Sturm; Hela Hundertmark; Axel Schmidt; Martina Kreiß; Tim M. Strom; Dagmar Wieczorek; Tobias B. Haack; et al. (Human Genetics, 2018)

Characterisation of the clinical and activated T cell response to repeat delayed-type hypersensitivity skin challenges in human subjects, with KLH and PPD, as a potential model to test T cell-targeted therapies - Alexandra Belson; Tim Schmidt; Disala Fernando; Kelly Hardes; Nicola Scott; Sara Brett; Deborah Clark; João Joaquim Oliveira; Bill Davis; Simon McHugh; John Stone (Inflammation Research, 2016)

Prediction uncertainty of environmental change effects on temperate European biodiversity - Carsten F. Dormann; Oliver Schweiger; P. Arens; I. Augenstein; St. Aviron; Debra Bailey; J. Baudry; R. Billeter; R. Bugter; R. Bukácek; F. Burel; M. Cerny; et al. (Ecology Letters, 2008)
Observed patterns of species richness at landscape scale (gamma diversity) cannot always be attributed to a specific set of explanatory variables, but rather different alternative explanatory statistical models of similar quality may exist. Therefore predictions of the effects of environmental change (such as in climate or land cover) on biodiversity may differ considerably, depending on the chosen set of explanatory variables. Here we use multimodel prediction to evaluate effects of climate, land‐use intensity and landscape structure on species richness in each of seven groups of organisms (plants, birds, spiders, wild bees, ground beetles, true bugs and hoverflies) in temperate Europe. We contrast this approach with traditional best‐model predictions, which we show, using cross‐validation, to have inferior prediction accuracy. Multimodel inference changed the importance of some environmental variables in comparison with the best model, and accordingly gave deviating predictions for environmental change effects. Overall, prediction uncertainty for the multimodel approach was only slightly higher than that of the best model, and absolute changes in predicted species richness were also comparable. Richness predictions varied generally more for the impact of climate change than for land‐use change at the coarse scale of our study. Overall, our study indicates that the uncertainty introduced to environmental change predictions through uncertainty in model selection both qualitatively and quantitatively affects species richness projections.

Rationale and design of the National Program of Cancer Registries' breast, colon, and prostate cancer patterns of care study - Kathleen McDavid; Maria J. Schymura; Lori Armstrong; Loretta Santilli; Beth Schmidt; Tim Byers; C. Brooke. Steele; Lilia O'Connor; Nancy C. Schlag; Winny Roshala; Dottie Darcy; Genevieve Matanoski; et al. (Cancer Causes & Control, 2004)

The outwardly rectifying chloride channel in rat peritoneal mast cells is regulated by serine/threonine kinases and phosphatases - Jörg Seebeck; Stefan Tritschler; Tim Roloff; Marie-Luise Kruse; Wolfgang E. Schmidt; Albrecht Ziegler (Pflügers Archiv - European Journal of Physiology, 2002)